Quantitative Detection of t(14;18)-Positive Cells by Real-Time Quantitative PCR Using Fluorogenic Probes - Dölken Lars; Schüler Frank; Dölken Gottfried (BioTechniques)
To detect t(14;18)-positive cells present in human lymphoma tissue, bone marrow aspirates and peripheral blood mononuclear cells (PBMNC), we have established an automated, real-time quantitative PCR using double-labeled fluorogenic probes. In relation to t(14;18)-positive genomic DNA or a cloned t(14;18)-DNA fragment, highly reproducible results can be obtained with initial copy numbers between 10 to 105. The detection of single copies has been verified by the stochastic multiple-tube approach. PBMNC cells obtained during clinical follow-up of patients with follicular lymphoma were analyzed by the one-step, real-time quantitative PCR and a two-step, semi-nested PCR combined with a limiting dilution assay. The quantitative results obtained by both assays correlate very well. Real-time quantitative PCR has several advantages: (i) it involves less critical pipetting steps, (ii) is less timeconsuming and (iii) UTP, in combination with uracil-N-glycosylase, can be used to control carryover contamination. The higher specificity is due to optimized primer annealing conditions and MgCl2 concentration and the use of AmpliTaq Gold™. The sensitivity is at least as high as by the two-step PCR. Real-time quantitative PCR will be very helpful in large epidemiological studies and in research for molecular staging and the detection of minimal residual tumor cells, including the analysis of blood stem-cell preparations to be used for transplantation after myelo-ablative therapy.